A comprehensive energy, exergy and enviroeconomic (3-E) analysis with carbon mitigation for multistage evaporation assisted milk powder production unit. (February 2021) - Singh, Gurjeet; Chopra, K.; Tyagi, V.V.; Pandey, A.K.; Ma, Zhenjun; Ren, Haoshan
Graphical abstract: Highlights: Presents thermodynamic assessment of multistage evaporation assisted milk powder production unit. The overall exergy efficiency was calculated as 63.56%. The SExD and SExIP were estimated to be 1724.06 kJ/kg and 702.40 kJ/kg respectively. The SC/WE and SSC were diagnosed to be 1.22 kg/kg and 0.74 kg/kg respectively. The adoption of PV Panel Technology assisted in 17, 670 Tonnes CO2 mitigation during lifetime. Abstract: The global annual milk powder trade was estimated to be of 851.84 Million Metric Tons whereas; its Indian counterpart was recorded as 196.18 Million Metric Tons in the year 2019. The world's annual milk powder production has registered a growth of 50% in the last three decades. In view of high thermal and electrical energy consumption; the present work focus upon energy, exergy and enviroeconomic assessments for comprehensive powder production wherein, the value of exergy efficiency, specific exergy destruction and specific exergy improvement potential. The exergetic performances of triple effect evaporator and single stage spray dryer unit were computed as 56.62% and 66.11% respectively. Additionally, involvement of economic approach with total saving in uniform yearly cost through electricity from PV panels will be approximately calculated as 979, 006 and 874, 319 at an interest rates of 4.5% and 7.5% respectively. Similarly, the investment on PV panels will be recovered after 8 and 11 years of operation for the respective rates of interests. On the basis environmental evaluation, it was found that adoption of clean energy solution (PV panels); could assist in mitigation of approximately 17, 670 Tonnes of CO2 during its lifetime with securing a revenue of 256, 215 /lifetime.